Violence against women in Costa Rica: A criminological analysis of femicide as a criminal category and structural violence - Villareal Salazar, Jéssica (2025)
Violence against women in Costa Rica is a complex phenomenon that manifests itself in various forms, including physical, sexual, psychological, and economic violence. This problem not only affects women individually, but also perpetuates structures of gender inequality in Costa Rican society. Despite legislative advances, such as the inclusion of femicide in the criminal framework, significant challenges persist due to the lack of studies that address violence from a gender perspective and budget cuts that limit prevention and care initiatives. The methodological analysis of this study is based on a qualitative and descriptive approach, using statistics from the Judiciary and related legislation. The importance of collecting detailed data on femicide cases is highlighted, which is crucial for effective policy formulation. Furthermore, it is proposed that education in Human Rights and gender is essential to build a more equitable society. Preventive proposals include training programs and zero tolerance policies towards violence, with the aim of mitigating femicidal violence and promoting a paradigm shift in the perception and treatment of this social problem.